2013
DOI: 10.7554/elife.00411
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM visualization of the ribosome in termination complex with apo-RF3 and RF1

Abstract: Termination of messenger RNA translation in Bacteria and Archaea is initiated by release factors (RFs) 1 or 2 recognizing a stop codon in the ribosomal A site and releasing the peptide from the P-site transfer RNA. After release, RF-dissociation is facilitated by the G-protein RF3. Structures of ribosomal complexes with RF1 or RF2 alone or with RF3 alone—RF3 bound to a non-hydrolyzable GTP-analog—have been reported. Here, we present the cryo-EM structure of a post-termination ribosome containing both apo-RF3 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
50
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 54 publications
(136 reference statements)
7
50
1
Order By: Relevance
“…3B, lane 8), while His-tagged RF1 binding is substantially diminished in the presence of RF3:GTP and RF3:GDPNP (lanes 12,16). These data are consistent with a model in which the GTPbound form of RF3 stabilizes a conformational state of the ribosome that promotes RF1 dissociation as previously reported (Gao et al 2007;Jin et al 2011;Zhou et al 2012b;Pallesen et al 2013). …”
Section: Interactions Between Rf3:nucleotide and Ribosome Complexessupporting
confidence: 92%
See 3 more Smart Citations
“…3B, lane 8), while His-tagged RF1 binding is substantially diminished in the presence of RF3:GTP and RF3:GDPNP (lanes 12,16). These data are consistent with a model in which the GTPbound form of RF3 stabilizes a conformational state of the ribosome that promotes RF1 dissociation as previously reported (Gao et al 2007;Jin et al 2011;Zhou et al 2012b;Pallesen et al 2013). …”
Section: Interactions Between Rf3:nucleotide and Ribosome Complexessupporting
confidence: 92%
“…1). Other studies have similarly attempted to remove bound nucleotide (Pallesen et al 2013;Peske et al 2013). Most recently, Wintermeyer and colleagues demonstrated by FPLC the loss of bound nucleotide but found that RF3 activity was then diminished (Peske et al 2013).…”
Section: Gtp and Gdp Bind Rf3 With Similar Affinitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…11,14 Thus, a majority of structural data connect uL11 with the elongation cycle of protein synthesis. However, several structural analyses implicate this protein in interaction with IF2 and RF3, indicating involvement of uL11 in the initiation and termination steps of translation, 15,16 which is also supported by several functional analyses. 17,18 The large ribosomal subunit depleted of this protein is able to bind initiation factor IF2 in vitro but it cannot stimulate GTP hydrolysis required for the subunit joining.…”
Section: Introductionmentioning
confidence: 64%